Robust exponential stability of linear neutral system with constant neutral and time-varying discrete delays - Thaned Rojsiraphisal (2018)
In this paper, an exponentially stable condition for linear neu-tral with uncertainties and constant neutral and time-varying discrete delays is formulated. Based on a change of variable and improved Lyapunov-Krasovskii functional, the sufficient condition is obtained in the form of linear matrix inequalities. Two numerical examples are given to show effectiveness of the proposed condition by comparing upper bounds of the time-delays and rate of convergence with recent works. © 2013 Academic Publications, Ltd.